The EC's pre-accession aid to Portugal: A critical look - Michael Dauderstädt (Intereconomics, 1986)
Many experts expect Portugal's and Spain's integration into the EC to have a basically negative effect on their economies. Positive effects are expected essentially to be a result of the EC's aid programmes. An indication as to how far the aid will in fact help to promote adjustment and modernization in the new Southern European member countries is shown by the following critical analysis of the aid programmes to date to Portugal.
Keywords: 330; European Community